An exploratory study for the impact of video-induced positive moods on ideation. Issue 1 (2nd January 2023) - Masaya, Shogo; Fujii, Kenichi; Watanabe, Kazunori; Chen, Chao; Hai, Liang; Zhang, Jiawei; Ohkubo, Tomoyuki; Murakoshi, Hideki; Hirose, Yuta
ABSTRACT: This paper examines the impact of positive moods induced by video content on creativity in ideation. Previous studies have shown that positive moods can promote ideation with originality and diversity and videos that promote feelings happiness or relaxation can induce positive feelings as visual stimuli. Building upon these findings, in this study, we developed an online experimental system and conducted experiments on ideation under the following four stimulus conditions: 1) no stimulus, 2) text stimulus, 3) image stimulus and 4) video stimulus. The experiment was designed using alternate uses task, and the participants' performance on ideation was then compared with their performance in the presence of each stimulus from the perspective of enhancing creativity. The results demonstrated that video-induced stimuli promoting happiness or relaxation exhibited a relatively high potential to enhance ideation with originality.